The Holocaust, corporations and the law : unfinished business - Bilsky, Leora, 1967- (Law, meaning, and violence., 2017)
The Holocaust, Corporations, and the Law explores the challenge posed by the Holocaust to legal and political thought by examining the issues raised by the restitution class action suits brought against Swiss banks and German corporations before American federal courts in the 1990s. Although the suits were settled for unprecedented amounts of money, the defendants did not formally assume any legal responsibility. Thus, the lawsuits were bitterly criticized by lawyers for betraying justice and by historians for distorting history. Leora Bilsky argues class action litigation and settlement offer a mode of accountability well suited to addressing the bureaucratic nature of business involvement in atrocities. Prior to these lawsuits, legal treatment of the Holocaust was dominated by criminal law and its individualistic assumptions, consistently failing to relate to the structural aspects of Nazi crimes. Engaging critically with contemporary debates about corporate responsibility for human rights violations and assumptions about "law," she argues for the need to design processes that make multinational corporations accountable, and examines the implications for transitional justice, the relationship between law and history, and for community and representation in a post-national world. In an era when corporations are ever more powerful and international, Bilsky's arguments will attract attention beyond those interested in the Holocaust and its long shadow.